Optical spectroscopy of single perovskite nanocrystals for quantum photonics - Mohamed-Raouf Amara (Nanyang Technological University, 2023)
Lead halide perovskites in their nanocrystal form have recently emerged as efficient quantum light emitters despite their low-temperature colloidal synthesis and structural lability. This has led to an intense debate about the band-edge exciton in these materials and the bright or dark character of the lowest energy exciton state. While symmetry arguments predict a lowest-lying dark exciton state, it was hypothesised that the combination of strong-spin orbit and structural instability should lead to a Rashba effect which places the bright exciton state below the dark exciton, in contrast with all other established materials. This work is a detailed study of single CsPbBr3, in the spectral and time domain, which provides critical information about the band-edge exciton fine structure. It should help the community refine theoretical models and converge towards an accurate description of the band-edge exciton of these fledgling materials, thus helping to shed light on their outstanding properties.